The Result of Validation Test of Student’s Book Based on Inquiry of Science Learning for Student of Class VIII SMP - Fitri Arsih; Yuni Ahda (Bioeducation Journal, 2017)
This study aimed to analyze the results of student books based on inquiry validation for class VIII Junior High School. Validation was done by 6 validators consisting of three lecturer and three teachers. Data obtained from the questionnaire validation. The questionnaire results were analyzed with descriptive analysis. The analysis showed that the average student book based inquiry validation results were 91.51 with very valid criteria. It can be concluded that the students books based on inquiry can be used to science teaching for students of class VIII Junior High School.